Diagnosis and management of xerostomia in patients with COVID-19 (Research, Society and Development, 2022)
Xerostomia or dry mouth is a change found routinely in clinical dental practice, this change directly affects the patient's quality of life, manifesting difficulties in tasting, chewing, speaking, swallowing and causing a lot of discomfort in the oral cavity. However, after the onset of the COVID-19 pandemic, researchers noticed a large complaint of infected patients reporting the sensation of dry mouth. The main objective of this study is to evaluate the way that xerostomia affects patients with COVID-19. The study was carried out through a literature review, searching Google Scholar, PubMed, and SciELO articles using the descriptors: “Oral Manifestations”; “Xerostomia” and “COVID-19”. All articles were selected by year, title, abstract, full text and, finally, all selected articles were processed for final review. 20 selected articles were obtained from the initial bibliographic research of 295 articles, reports obtained from the selected studies demonstrate that xerostomia has a high incidence in patients who were infected by COVID-19, which directly impacts their quality of life and the way that they react to the treatments when they are submitted to hospital treatments, however, other oral manifestations appear strongly, which causes a greater debilitation in the patient's systemic health. Oral manifestations, such as xerostomia, taste problems, inflammation of the salivary glands, duly mentioned in the study, are typically reported in patients who had a viral infection by Sars-CoV-2, and it is worth noting that, regardless of the pathogenesis of these manifestations, the importance of developing specific protocols.